Caracterización de los mecanismos cinéticos y de transferencia de momentum, calor y masa en un biorreactor de fermentación en medio sólido utilizando subproductos agroindustriales - Gómez Ramos, Gerardo Atlantis (Universidad Autónoma Metropolitana, 2021)
The objective of this work was the development and implementation of experimental and numerical methodologies that would allow characterizing: hydrodynamics (fluid dynamics), heat and mass transfer under abiotic conditions in a packed tray bioreactor with wall cooling at bench scale. using agroindustrial by-products as substrate; and kinetics (biotic experiments) using Yarrowia lipolytica 2.2ab as microorganism. The characterization was evaluated at operating conditions of industrial interest: wall temperatures of 298.15 K - 318.15 K, initial moisture content of 6 - 60% and specific volumetric air flows of 1.25 - 62.50 Laire.kgss –1 .min–1 . In fluid dynamics, a model was developed that describes the velocity profiles of the fluid, the characterization of viscous and inertial resistances due to the interaction between the solid and the fluid in the regions of the core and the wall of the packed tray: two zones model (TZM). The TZM reduced the computation time (under the same computational conditions) by describing the same velocity profiles by 3000 to 3600% compared to a conventional hydrodynamic model (Navier-Stokes-Darcy-Forchheimer equations). In heat transfer, the parameters of effective thermal conductivity (keff) and the heat transfer coefficient in the wall (hw) in steady and transient state were estimated, this through experimental temperature data, incorporating the velocity profiles obtained with the TZM. The keff results obtained for the steady state are in a range from 1.24 x10-4 to 9.05 x10-4 W.m-1 .K-1 while for the transitory state it is in the range of 6.21 x10-1 to 2.11 x10-1 W.m-1 .K-1 ; on the other hand, hw in steady state ranges from 3.10 x101 to 7.501 x101 W.m-2 .K-1 , while for the transitory state it ranges from 6.57 x100 to 4.78 x102 W.m-2 .K-1 . The parameters were also determined considering an approximation of plug flow velocity, finding results with two orders of magnitude lower than that obtained with the velocity profiles of the TZM. In mass transfer, dispersion coefficients (Deff) were estimated with O2 concentration data. The Deff results ranged from 2.59 x10-3 to 5.28 x10-3 m2 .s-1 . The biotic analysis (kinetics) was characterized by determining the specific kinetic descriptors of the growth of the microorganism with experimental data of CO2 production and O2 consumption. Results were obtained for CO2max of 213.11 mgCO2.gms -1 ,  of  h −  2 2 YCO O/ of 0.65 mgO2.mgCO2 -1 and mO2 of 1.51x10-3 mgO2 mgCO2 -1 h -1 . Finally, the individually obtained descriptors were integrated into a two-phase pseudoheterogeneous model (fluid and solid phase), which allows to characterize the kinetics and heat and mass transport phenomena. The simulations of the process show positive results, particularly in the concentration of CO2, O2 and H2O up to 12 hours after the start of the fermentation in solid medium, an area where the maximum production of CO2 is reached.; Este trabajo tuvo como objetivo el desarrollo e implementación de metodologías experimentales y numéricas que permitieran caracterizar: la hidrodinámica (dinámica de fluidos), transferencia de calor y masa en condiciones abióticas en un biorreactor de charola empacado con enfriamiento en la pared a escala de banco utilizando como sustrato subproductos agroindustriales; y cinética (experimentos bióticos) utilizando Yarrowia lipolytica 2.2ab como microorganismo. La caracterización se evaluó a condiciones de operación de interés industrial: temperaturas de pared de 298.15 K – 318.15 K, contenido de humedad inicial de 6 – 60% y flujos volumétricos específicos de aire de 1.25 – 62.50 Laire.kgss ̄¹ .min ̄¹ . En la dinámica de fluidos se desarrolló un modelo que describe los perfiles de velocidad del fluido, la caracterización de resistencias viscosas e inerciales debido a la interacción entre el sólido y el fluido en las regiones del núcleo y la pared de la bandeja empaquetada: modelo de dos zonas (TZM por sus siglas en inglés). El TZM redujo el tiempo de cálculo (bajo las mismas condiciones de cómputo) al describir los mismos perfiles de velocidad en un 3000 a 3600 % en comparación con un modelo hidrodinámico convencional (ecuaciones de NavierStokes-Darcy-Forchheimer). En transferencia de calor se estimaron los parámetros de conductividad térmica efectiva (keff) y el coeficiente de transferencia de calor en la pared (hw) en estado estacionario y transitorio, esto mediante datos experimentales de temperatura, incorporando los perfiles de velocidad obtenidos con el TZM. Los resultados de keff obtenida para el estado estacionario se encuentra en un rango de 1.24 x10-4 a 9.05 x10-4 W.m ̄¹ . K ̄¹ mientras que para el estado transitorio se encuentra en el rango de 6.21 x10 ̄¹ a 2.11 x10-1 W.m ̄¹ . K ̄¹ ; por otra parte, hw en estado estacionario oscila desde 3.10 x101 a 7.501 x101 W.m ̄⁴ . K ̄¹ , mientras que para el estado transitorio oscila desde de 6.57 x100 a 4.78 x102 W.m ̄² .K ̄¹ . Los parámetros también se determinaron considerando una aproximación de velocidad de flujo pistón, encontrando resultados con dos órdenes de magnitud menores respecto a lo obtenido con los perfiles de velocidad del TZM.En transferencia de masa se estimaron los coeficientes de dispersión (Deff) con datos de concentración de O2. Los resultados Deff oscilaron entre 2.595 x 10 -3 y 5.286 x 10 -3 m2 .s -1 . El análisis biótico (cinética) se caracterizó determinando los descriptores cinéticos específicos del crecimiento del microorganismo con datos experimentales de producción de CO₂ y consumo de O₂. Se obtuvieron resultados de CO₂max de 213.11 mgCO2.gms -1 ,  de  h −  2 2 YCO O/ de 0.65 mgO2.mgCO2 -1 y mO2 de 1.51x10-3 mgO2 mgCO₂ -1 h -1 . Finalmente se integraron los descriptores obtenidos individualmente a un modelo pseudoheterogéneo de dos fases (fase fluida y sólida) que permite caracterizar la cinética y los fenómenos de transporte de calor y masa. Las simulaciones del proceso presentan resultados positivos, particularmente en la concentración de CO₂, O₂ y H₂O hasta las 12 horas de iniciada la fermentación en medio sólido, zona donde se alcanza la máxima producción de CO₂.